Clinical and Oncological Value of Preoperative BMI in Gastric Cancer Patients: A Single Center Experience. (10th February 2015) - Voglino, Costantino; Di Mare, Giulio; Ferrara, Francesco; De Franco, Lorenzo; Roviello, Franco; Marrelli, Daniele
Abstract : Introduction . The impact of preoperative BMI on surgical outcomes and long-term survival of gastric cancer patients was investigated in various reports with contrasting results. Materials & Methods . A total of 378 patients who underwent a surgical resection for primary gastric cancer between 1994 and 2011 were retrospectively studied. Patients were stratified according to BMI into a normal group (<25, group A), an overweight group (25–30, group B), and an obesity group (≥30, group C). These 3 groups were compared according to clinical-pathological characteristics, surgical treatment, and long-term survival. Results . No significant correlations between BMI and TNM (2010), UICC stage (2010), Lauren's histological type, surgical results, lymph node dissection, and postoperative morbidity and mortality were observed. Factors related to higher BMI were male gender P < 0.05, diabetes P < 0.001, and serum blood proteins P < 0.01 . A trend to fewer lymph nodes retrieved during gastrectomy with lymphadenectomy in overweight patients (B and C groups) was observed, although not statistically significant. There was no difference in overall survival or disease-specific survival between the three groups. Conclusion . According to our data, BMI should not be considered a significant predictor of postoperative complications or long-term result in gastric cancer patients.